2015
DOI: 10.1038/srep17295
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Spinach Array for mRNA Imaging in Living Bacterial Cells

Abstract: Live cell RNA imaging using genetically encoded fluorescent labels is an important tool for monitoring RNA activities. A recently reported RNA aptamer-fluorogen system, the Spinach, in which an RNA aptamer binds and induces the fluorescence of a GFP-like 3,5-difluoro-4-hydroxybenzylidene imidazolinone (DFHBI) ligand, can be readily tagged to the RNA of interest. Although the aptamer–fluorogen system is sufficient for imaging highly abundant non-coding RNAs (tRNAs, rRNAs, etc.), it performs poorly for mRNA imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(108 citation statements)
references
References 63 publications
2
106
0
Order By: Relevance
“…Since then, new aptamer systems have been developed, including Spinach 2 (53), Mango (54), Broccoli (55, 56), and Corn (57). Repetitive Spinach aptamers have been shown to increase the brightness by a maximum of 17-fold (with 64 repeats) compared to a single Spinach monomer at a cost of a significant lengthening of the aptamer sequence (58). Alternatively, the fluorogenic small molecules have been designed into a covalently linked fluorophore-quencher pair, and the aptamers are selected to either bind the quencher or the fluorophore.…”
Section: Approaches To Study Rna Localizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, new aptamer systems have been developed, including Spinach 2 (53), Mango (54), Broccoli (55, 56), and Corn (57). Repetitive Spinach aptamers have been shown to increase the brightness by a maximum of 17-fold (with 64 repeats) compared to a single Spinach monomer at a cost of a significant lengthening of the aptamer sequence (58). Alternatively, the fluorogenic small molecules have been designed into a covalently linked fluorophore-quencher pair, and the aptamers are selected to either bind the quencher or the fluorophore.…”
Section: Approaches To Study Rna Localizationmentioning
confidence: 99%
“…(C) The Spinach aptamer and its application to image mRNAs in live E.coli cells. The image is adapted from (58) (licensed under a Creative Commons Attribution 4.0 International License: http://creativecommons.org/licenses/by/4.0/), in which a tandem array of Spinach aptamers is fused to the RNA of interest to enhance the signal, and fluorescent detection upon addition of the organic ligand DFHBI.…”
Section: Figurementioning
confidence: 99%
“…It has been demonstrated that fluorescent RNA molecules, named Spinach and Broccoli, can be employed as genetically encoded reporters for RNAimaging. 2022 Spinach and Broccoli are RNA aptamers that can bind and activate the fluorescence of small-molecule dyes, such as 3,5-difluoro-4-hydroxybenzylidene-1-trifluoroethyl-imidazolinone (DFHBI-1T). 2325 Recently, the Ellington group has successfully demonstrated that Spinach can function as a reporter in an RNA-based CHA reaction in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, DFHBI can bind to Spinach aptamer-fused 5S RNAs and image their live-cell dynamics 47 . Furthermore, a tandem Spinach array shows up to about 17-fold higher fluorescence by accommodating 8–64 repeats of Spinach aptamers in target RNAs 48 . However, the Spinach aptamer-DFHBI system suffers from limited folding efficiency and thermal instability.…”
Section: Probes Imaging Exogenous Rnasmentioning
confidence: 99%